Artificial Defoliaton of Cowpea [Vigna unguiculata (L.) Walp.] cv. Ife Brown to Simulate Insect Damage: Effects on Crop Performance - Akingbohungbe, A. E. (Faculty of Agriculture, University of Ife, 2015)
The effects of defoliation on cowpea, Vigna unguiculata (L.) Walp cv. Ife Brown, were studied in the screenhouse by removing varying proportions of the laminae of leaflet along-the transverse plane, to give varying nominal levels of defoliation. Plants subjected once to 25%, SO%, 75% and 100% defoliation at either the primary leaf stage, the first trifoliate leaf stage or the second trifoliate leaf stage, were not adversely affected with respect to days to peak flowering, number of flowers per plant, number of pods per plant as well as number and weight of seeds per plant. However, 100% defoliation significantly delayed the days to first flower production. When plants were subjected to 25%, 50% and 75% nominal defoliation once a week for a period of three weeks, commencing at the first trifoliate leaf stage, significant treatment effects were observed with the 75% defoliation adversely affecting the number of pods per plant, number and weight of seeds per plant. I t was also observed that defoliated leaflets tended to compensate by increasing their widths. The importance of the results are discussed in relation to the impact of defoliators and recommendation's for their control in cowpea production.